For good or glory? - an investigation on what one can learn from a current Swedish architecture debate about aesthetics and perception of architecture - Lidenholm, Maria-Therese (My University, 2020)
In the beginning of my architecture education I remember my grandmother once said to me ”you’re not going to draw such boring boxes, aren’t you Maria?”. It was a result of her telling me about a new-built residential house in the area where she lives. Ever since that I have, now and then, encountered comments about architecture from people I know. It is probably because they know that I am studying architecture and it therefore feels natural to talk to me about it. At the same time, during the last decade civic movements discussing architecture have grown large and formed a new architecture debate in Sweden. People do seem to actually have opinions about their built environment. They do not necessarily analyse architecture on a daily basis, but when presenting a proposal for a new building people react, when travelling people form a perception about the local architecture and when looking for a new home certain architectural values matter. In the current Swedish architecture debate the views fall apart regarding the aesthetics, style and quality of what is built today. Certain non-architects are criticizing it, while certain architects are defending it. Architecture is the only art form we cannot escape from. Whether we think about it or not, we are constantly surrounded and influenced by it. What good architecture is depends on whom you ask. This thesis investigates how architecture is perceived among non-architects and architects and what we can learn from today’s architecture debate about aesthetics and style. Through research and design the goal is to get an increased awareness and better understanding on what kind of architecture is appreciated among people today and, by giving the debate another dimension, raise the question of whom we are building for - for others good or for our own glory?
Keywords: perception, aesthetics, non-architect vs architect, dialogue, design tool